Causality between major depressive disorder and functional dyspepsia: a two-sample Mendelian randomization study - Du, Yaming; Wang, Rui; Xu, Xinzi; Wang, Junli; Shao, Wei; Chen, Guohua (Frontiers in Neurology, 2024)
Background To investigate the causal relationship between major depression and functional dyspepsia using two-sample Mendelian randomization. Methods Data for major depression and functional dyspepsia were obtained from genome-wide association studies. We selected Single Nucleotide Polymorphisms (SNPs) strongly associated with severe depression. Mendelian randomization analysis was conducted using methods such as Inverse-Variance Weighted (IVW), MR-Egger, and Weighted Median Estimator (WME). Sensitivity analysis was performed to assess the robustness of the results. Results A total of 31 eligible SNPs were identified as instrumental variables for major depression. IVW analysis indicated a positive causal relationship between the two conditions (β = 0.328; SE = 0.137; p = 0.017), suggesting that severe depression increases the risk of functional dyspepsia (OR = 1.389; 95% CI: 1.062–1.816). Sensitivity tests showed no evidence of heterogeneity or horizontal pleiotropy (p > 0.05). Conclusion MR analysis had shown that major depressive disorder is associated with an increased risk of functional dyspepsia.